Strengthening Tolerance Attitude through Jaga Sesama Community - Erna Gesti Fadrusiana; Rini Triastuti; Winarno Winarno (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Various cases of religious and social intolerance reflect that Indonesian society needs to improve and strengthen tolerance. Several ways are taken so that tolerance can be instilled and strengthened through both formal and informal aspects. From an informal perspective, the community has a way to instill tolerance through community activities including Jaga Sesama community. The purpose of this study was to determine the strengthening of tolerance through the Community Watch Guard conducted by using qualitative methods and purposive sampling techniques. The research subjects were members of Jaga Sesama community. Data collection techniques by interview and observation. The results of the study showed that community activities such as Reading Qur’an and Mbois (Discussion Islamic Chat) helped strengthen the tolerance of the Surakarta community which was shown through mutual respect, mutual respect for each other or different religions, accepting differences and always maintaining harmony that could strengthen unity and integrity.